Urinary tract infection in Hemodialysis patients with renal failure - Manhal, Falah S.; Mohammed, Ammer A.; Ali, Kais H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Urinary tract infections (UTIs) are common in dialysis patients, are associated with increased rate of complications, and may be difficult to diagnose due to often subclinical presentation. Objectives: To examine theprevalence of urinary tract infections in hemodialysis patients with renal failure, and to evaluate the diagnostic accuracy of pyuria as a screening test in hemodialysis patients. Patients and Methods: A total of forty hemodialysis patients (27 males and 13 females) with renal failure were selected according to the study criteria. Clean-catch mid-stream urine specimens were obtained from study patients, their urinalysis and bacterial culture were performed according to standard techniques. Bacteriuria is defined as detection of  105 cfu/ml of a single microorganismin culture of urine specimens.Pyuria is defined as the presence of 10 neutrophils per high power field of voided mid-stream urine. Results: Urine from 25(62%) patients had no significant organism growth, whereasurine from 15(37%) patients grew  105 cfu/ml; 6 patients had been infected with E. coli, 5 patients with Klebsiella spp., one patient with Acinetobacter, one patient with α-hemolytic Streptococci, one patient with coagulase negative Staphylococci, and one patient with Proteus spp.. Fourteenout of 40 (35%) patients had pyuria and only 9 (64%) out of 14 patients had a positive urine culture for infection. The sensitivity and specificity of pyuria screening for UTI was 60% and 80%, respectively. The positive and negative predictive values are 64% and 77%, respectively. Conclusions: The result of this study demonstrates that pyuria was a good marker for significant bacteriuria in these patients. Cultural techniques are needed for susceptibility testing of bacterial isolates to guide antimicrobial therapy. The antimicrobial susceptibility tests in this study revealed that Amikacin, Gentamicin, Ceftazidime, Cefoxitin, and Imipenem act well on isolated bacteria.